Optimization of Recruitment of Prospective Financial Managers Through a Decision Support System with the Multi Attribute Utility Theory Method - Firmansyah, Muhammad Raafi'u; Sahara, Sahara; Yeyi Gusla Nengsih; Dedi Rahman Habibie; Yohani Setiya Rafika Nur (Politeknik Piksi Ganesha Indonesia, 2024)
This study evaluates the application of Multi Attribute Utility Theory (MAUT)-based decision support systems in the recruitment process of financial managers in technology companies